VEGF-A Expression in Preeclampsia Rats’ Liver Treated with Andaliman Seed (Zanthoxylum acanthopodium DC.) Extract - Khoirunnisa', Raniah; Safa, Muhammad Shafala; Noer, Azmi; Virgirinia, Regina Putri; Fatchiyah, Fatchiyah (Graduate School, Universitas Brawijaya, 2026)
Preeclampsia is a life-threatening pregnancy disorder diagnosed after 20 weeks of gestation, characterized by hypertension (≥140/90 mmHg) and often accompanied by proteinuria (≥300 mg.24 hours-1). Preeclampsia causes an imbalance in angiogenic factors, increasing levels of soluble fms-like tyrosine kinase-1 (sFlt-1), which reduces the expression of Vascular Endothelial Growth Factor (VEGF-A) protein. This condition affects other organs, such as the liver, causing hypoxia. Andaliman (Zanthoxylum acanthopodium DC.), rich in bioactive compounds, is a potential alternative treatment for preeclampsia due to its hepatoprotective, anti-inflammatory, and angiogenic-modulating effects. This study aims to identify changes in VEGF-A protein expression in the liver of a preeclampsia rat model (Rattus norvegicus), divided into four groups, with treatment using Andaliman seed extract. Protein was extracted from the liver and measured using the Bradford method, followed by SDS-PAGE and retardation factor (RF) calculation, and then continued with Western blotting. Band intensity data were analysed quantitatively. The results showed that the preeclampsia group had a lower VEGF-A fold change (0.67 ± 0.28) than the control group (1.00). This indicates a decrease in VEGF-A expression, possibly due to an increase in the anti-angiogenic factor sFlt-1. A dose of 100 mg.kg-1 body weight of Andaliman extract (0.96 ± 0.08) was more effective than 200 mg.kg-1 body weight (0.78 ± 0.24) because it increased the protein intensity of VEGF-A based on western blotting. These findings suggest that Andaliman seed extract, particularly at a dose of 100 mg.kg-1 body weight, has potential as a hepatoprotective agent in preeclampsia through the restoration of VEGF-A expression.